DETERMINASI EFISIENSI INVESTASI PADA PERUSAHAAN DI INDONESIA - Vina Pandu Wijaya; Ari Dewi Cahyati (Universitas Budi Luhur, 2021)
This purpose of this study was to determine the effect of corporate governance, ownership structure and debt maturity on investment efficiency. The sample in this study is a manufacturing sector company listed on the Indonesia Stock Exchange in 2015- 2019. The sampling technique in this study uses the purposive sampling method, where there are 42 companies that meet predetermined criteria. Results of this study indicates that the audit committee has no effect and is not significant on investment efficiency, independent board of commissioners has a significant positive effect on investment efficiency, managerial ownership variable has no significant effect on investment efficiency, institutional ownership variable has no and no significant effect on investment efficiency, debt maturity variable has a significant positive effect on investment efficiency.